2016
DOI: 10.1016/j.ccell.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Inflammation-Associated IL-17A Causes Non-alcoholic Steatohepatitis and Hepatocellular Carcinoma

Abstract: Obesity increases hepatocellular carcinoma (HCC) risks via unknown mediators. We report that hepatic unconventional prefoldin RPB5 interactor (URI) couples nutrient surpluses to inflammation and non-alcoholic steatohepatitis (NASH), a common cause of HCC. URI-induced DNA damage in hepatocytes triggers inflammation via T helper 17 (Th17) lymphocytes and interleukin 17A (IL-17A). This induces white adipose tissue neutrophil infiltration mediating insulin resistance (IR) and fatty acid release, stored in liver as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
297
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(330 citation statements)
references
References 43 publications
11
297
0
2
Order By: Relevance
“…The inflammatory response seems to be an important mediator of many NAFLD-associated outcomes such as the HCC by creating an inflammatory microenvironment (28, 51), cardiovascular disease by promoting atherogenesis (52, 53). Table 1 summarizes the clinical studies that have assessed the role of general inflammatory biomarkers and cytokines to predict outcomes in NAFLD.…”
Section: An Overview Of the Predictive Role Of General Inflammatory Bmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammatory response seems to be an important mediator of many NAFLD-associated outcomes such as the HCC by creating an inflammatory microenvironment (28, 51), cardiovascular disease by promoting atherogenesis (52, 53). Table 1 summarizes the clinical studies that have assessed the role of general inflammatory biomarkers and cytokines to predict outcomes in NAFLD.…”
Section: An Overview Of the Predictive Role Of General Inflammatory Bmentioning
confidence: 99%
“…Th17 cells secrete the IL-17, IL-21, and e IL-22, being important in immunity against extracellular infectious agents such as bacteria and fungi but also contribute in the immunopathogenesis of many diseases such as psoriasis and tumors (51, 9193). IL-17 is the most studied Th17-secreted cytokine in liver disease (15, 41, 42).…”
Section: Underlying Mechanisms Pathways and Relationship Between Cementioning
confidence: 99%
See 1 more Smart Citation
“…The crucial role of innate immunity in NASH-HCC development was supported by a recent study that demonstrated that the suppression of Th17 cell differentiation or blocking IL17A signaling prevents NASH and subsequent HCC development (9). Moreover, an elegant study emphasized the importance of gut microbiota in NASH progression and noted that senescent hepatic stellate cells (HSC) may be critical for the transformation of steatotic hepatocytes to malignant cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Because immune cells may induce different reactions between the skin and the liver, it is necessary to test the probiotics in an orthotopic model, as the authors are planning. Gomes et al recently reported that IL-17 promotes HCC by inducing insulin resistance in the adipose tissue (13), suggesting that additional mechanisms are involved in tumor suppression. However, the role of Th17 is not so simple.…”
Section: Editorial On Nutritionmentioning
confidence: 99%